2011
DOI: 10.1353/hpu.2011.0142
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Assessment of Barriers to Adoption of Dietary Approaches to Stop Hypertension (DASH) among African Americans of Low Socioeconomic Status

Abstract: Background We examined perceptions of Dietary Approaches to Stop Hypertension (DASH) and the food environment among African Americans (AA) with high blood pressure living in two low-income communities and objectively assessed local food outlets. Methods Focus groups were conducted with 30 AAs; participants discussed DASH and the availability of healthy foods in their community. Sessions were transcribed and themes identified. Fifty-four stores and 114 restaurants were assessed using the Nutrition Environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 26 publications
2
45
0
1
Order By: Relevance
“…In a previous study of price considerations for African Americans focused on all healthy foods, potential wastage and time cost for food preparation were concerns [16]. These same concerns arose in formative research prior to dietary intervention for African Americans with hypertension [24]. The present study, as well as others [1], shows that these factors apply specifically to the purchase and use of fruits and vegetables.…”
Section: Discussionsupporting
confidence: 51%
“…In a previous study of price considerations for African Americans focused on all healthy foods, potential wastage and time cost for food preparation were concerns [16]. These same concerns arose in formative research prior to dietary intervention for African Americans with hypertension [24]. The present study, as well as others [1], shows that these factors apply specifically to the purchase and use of fruits and vegetables.…”
Section: Discussionsupporting
confidence: 51%
“…3 These studies suggested that these adherence differences were likely influenced by food availability, cost, and culture and that additional adaptations and multilevel interventions may therefore be necessary to maximize impact of the DASH diet in African American communities. 3,8 This is consistent with research that has concluded that, to be effective in decreasing disparities, nutrition interventions must address a combination of individual, social, cultural, and environmental determinants. 9–18 …”
Section: Introductionsupporting
confidence: 75%
“…DASH clinical trials demonstrated a mean decrease of 5.5 mmHg in systolic blood pressure and 3.0 mmHg in diastolic blood pressure. 8 Participants in MOTMGC who reported “high participation” self-reported that they consumed more fruits and vegetables, seasoned their food with less sodium, and used less fat. There was a significant difference between the baseline and post-intervention samples in the intervention county of 4 mmHg in systolic and 2 mmHg in diastolic blood pressure, but not in the comparison county.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of these factors has led to sustainable adoption of healthy behaviors (intake of low-fat diets, increased physical activity) and reduction in cardiovascular risk in local communities in the United States. [10][11][12] buIldIng the evIdence base to address the global burden of hypertensIon…”
Section: Implementation Research To Address Hypertension -Peprah Et Almentioning
confidence: 99%